Online Peer Assessment in Nurturing Students Writing Skill - Pradana, Mahardhika; Rahmawati, Maya (FOSTER: Journal of English Language Teaching, 2021)
This study aims to investigate the process of online peer assessment implementation in a writing activity and to find out the students’ responses toward the implementation of online peer assessment in learning writing skills. This research uses a qualitative approach and case study as the research design. The data were collected with the triangulation data by observation, interview, and documentation. Observation checklist, in-depth interview, and documentation used as data retrieval instruments. The subject of this study is an English teacher and students of class XI TKJ 1 at SMKN 1 Rawamerta. The result of this study shows that the implementation of peer assessment in writing skills is very effective to help the students in learning writing and evaluating learning process. Before the implementation of peer assessment, the students were not able to recognize their mistakes in detail, they could only find out about the numerical score, and did not know about how to assess. Based on the result obtained, it is concluded that teaching writing to the students’ responses toward the use of peer assessment was positive. It can be seen from the attitude and enthusiasm. Students agreed that peer assessment is a very effective technique used in writing activities. It can be concluded that online peer assessment can be applied both in writing and speaking as well as an important part of the move towards more forms of participatory learning. There is a need to apply it in the schools and universities since it is more adaptable to modern developments in the assessment of learning outcomes.